Impact of corroded bars and spalling on the bond strength of reinforced concrete structures (2020)
The mechanism of the composite materials in Reinforced Concrete Structure is such that they both have to undergo the same stress and deformation as the surrounding, so as to prevent discontinuity, slip, or separation of both materials .Bond strength results from a combination of several parameters, such as the mutual adhesion between the concrete and steel interfaces and the pressure of the hardened concrete against the steel bar or wire due to the drying shrinkage of the concrete. A total of 24 singly reinforced beams with plain 10mm and 12mm steel rods were cast for this study. The beams were designed to fail by flexure and to allow bond slips occur before ultimate failure. The spalling effect was simulated by debonding the bars along its entire length with PVC pipes thus restricting concrete and steel contact. The beams are then subjected to flexural test by inducing a point load on its mid span. The results of the investigation reveals a slight increase in the bond strength of about 2.68% with the use of already corroded bars and the bond strength decreased by 39.2% and 81.8% for bars that had 25% and 50% of their perimeters debonded. The increase in bond strength with the use of corroded bars can be ascribed to the increased frictional resistance owing to the corroded bars surface roughness. The loss of bond strength with decrease in contact area was as a result of the bar being unable to resist perpendicular stresses and was easily pushed out of the beam